2008
DOI: 10.1262/jrd.19123
|View full text |Cite
|
Sign up to set email alerts
|

A New Preparation Protocol for Measurement of Testicular Sperm Production

Abstract: Abstract. In studies of male reproductive toxicity, measuring daily sperm production is a quite important criterion. However, the accuracy of the values measured by the basic protocol is still controversial. In order to enhance the homogeneity of countable testicular sperm/spermatid heads, this report introduces a new enzymatic method with a subsequent detergent treatment. The testis of rat was firstly homogenized in phosphate-buffered saline. The homogenate (buffer mix) was then treated with collagenase and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Sperm head counts were performed using hemocytometer as described by Choi[12] with necessary modifications. The testis was removed and weighted.…”
Section: Methodsmentioning
confidence: 99%
“…Sperm head counts were performed using hemocytometer as described by Choi[12] with necessary modifications. The testis was removed and weighted.…”
Section: Methodsmentioning
confidence: 99%
“…The method used in this study had a low variability, as shown by the low CV. Other methods for lysis of cells have been published (Choi, Tsunekawa, Kanai, & Kurohmaru, 2008;Pacheco, Anderson, & Boekelheide, 2012). These protocols may offer improvements to that may be required if computer-assisted counting is to be used.…”
Section: Discussionmentioning
confidence: 99%